THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL COMMITMENT, MANAGEMENT SUPPORT ON INNOVATION PERFORMANCE IN INSURANCE COMPANIES - Aulia Sindiyeni Omdali Putri; Bayu Rahadi; Edy Hartono (IJEBD (International Journal of Entrepreneurship and Business Development))
Objective: The following study aims to explore the influence of transformational leadership, organizational commitment, and management support on innovation performance in insurance companies in Indonesia.